(untitled) (Research, Society and Development, 2025)
Continuing education is an essential component for emergency healthcare staff, as it allows them to keep their skills and knowledge up to date, improving the quality of care and patient safety. In a dynamic and unpredictable work environment, emergency healthcare staff need to be prepared to deal with complex and urgent situations, where rapid and accurate decision-making is crucial. In addition, continuing education is essential to ensure that healthcare staff are up to date on the latest guidelines and care protocols, as well as new technologies and equipment available. This is especially important in emergency services, where healthcare staff need to be prepared to deal with a wide range of medical conditions and injuries. The purpose of this article is to present a literature review on the importance of continuing education for emergency healthcare staff and to present strategies for implementing effective continuing education programs. In addition, the article also addresses the challenges and obstacles that emergency healthcare staff may face when attempting to implement continuing education programs, and presents practical solutions to overcome these challenges.